The career identity of young working fathers in dual-earner relationships: A family-relatedness of work decisions perspective - Crafford, Anne; Koekemoer, Eileen (Frontiers in Psychology, 2022)
Introduction: Taking on an identity lens, we explore how young working fathers (in the establishment phase of their careers), experience their careers in the context of their changing family roles (shifting ideologies of fathering). We propose that working fathers' work experiences, work decisions, and career identity are the product of social and cognitive processes in a dual-earner relationship. Methods This qualitative study was conducted using an interpretive, and qualitative survey. The data was collected amongst a purposive sample of 45 young South African, well-educated, working fathers, using semi-structured interviews, until data saturation was reached. Interviews were recorded, transcribed, and analysed using thematic analysis. Results The three main themes extracted from the data were: "the meaning of family identity," "the impact of family identity on career identity," and finally, "the types of negotiation scenarios" used by working fathers in dual-earner relationships, and how they balance the work-family challenges they face. Conclusion This study provides strong empirical support for the family-relatedness of the work decisions perspective, as we highlight the roles of working fathers as indicative of their family identities, and how these then influence their career decisions. Furthermore, our findings shed light on how dual-earner couples negotiate their work-family needs to foster positive work-family outcomes.